PEMBERDAYAAN KARUNIA-KARUNIA ROH DI KALANGAN AKTIVIS GEREJA - Andiane Andiane; Gregorius Suwito; Rudyanto Chandra (JOURNAL of THEOLOGICAL STUDENTS, 2020)
Empowerment of spiritual gifts is a series of efforts made by church leaders to encourage, facilitate, and equip God's people to find, develop and use the gifts that will produce maximum fruit of service. The researcher aims to determine the level of empowerment of spiritual gifts that have been carried out among the activists of the JKI Maranatha Ungaran church and what factors have caused the spiritual gifts to be not maximal. Based on the results of the quantitative and qualitative data testing described above on the five indicators, it can be concluded that the Empowerment of Spiritual Gifts Among Church Activists of JKI Maranatha Ungaran is quite high.